2010
DOI: 10.2118/99105-pa
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Oilwell Cement Formulations Aged in H2S-Containing Fluids

Abstract: Summary In the next few decades, the production of oil fields with high contents of associated sour gases will increase. For instance, it is estimated that 40% of the world's remaining gas reserves contain more than 2% of carbon dioxide (CO2) and/or more than 100 ppm of hydrogen sulphide (H2S). Therefore, investigations on technologies to produce such fields are of utmost importance. Because of the presence of corrosive gas, special attention has to be paid to the design and the selection of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Thus, as expected, ettringite is not observed in the carbonated zone as it is not stable due to the lower pH (<∼10.5) of the cement porewater in this region (Taylor, 1997). In addition, ettringite is unstable at T > 90-100 • C (Lecolier et al, 2006;Taylor, 1997) and therefore was not observed in previous high-temperature experiments by Jacquemet et al (2008).…”
Section: Step 1: H 2 S Ingressmentioning
confidence: 48%
See 2 more Smart Citations
“…Thus, as expected, ettringite is not observed in the carbonated zone as it is not stable due to the lower pH (<∼10.5) of the cement porewater in this region (Taylor, 1997). In addition, ettringite is unstable at T > 90-100 • C (Lecolier et al, 2006;Taylor, 1997) and therefore was not observed in previous high-temperature experiments by Jacquemet et al (2008).…”
Section: Step 1: H 2 S Ingressmentioning
confidence: 48%
“…The H 2 S pathway is favored in anoxic (reducing) conditions whereas the polysulfide pathway is favored in oxidized conditions (Rickard and Luther, 1997). The conversion of ferrite to pyrite has been observed in previous H 2 S-CO 2 studies using hydrated cement powders (Jacquemet et al, 2008) and solid cementitious materials (Lecolier et al, 2006); however, no reaction pathways were proposed. Further studies utilizing synchrotron spectroscopy techniques are currently in progress in order to better understand the specific reaction pathway of pyrite formation from ferrite.…”
Section: Step 2: Pyrite Formationmentioning
confidence: 88%
See 1 more Smart Citation
“…The measured permeability of Portland cement exposed to H 2 S for 12 months, and aged at 120°C and 0.7 MPa has been reported to be 20 μd. [26] UCS measurements In Table 6, the UCS of the specimens is tabulated. The specimens were exposed to the different chemicals during time intervals previously specified.…”
Section: Permeabilitymentioning
confidence: 99%
“…There have been some long-term integrity studies of cement in other relevant downhole environments as well (Noik and Rivereau, 1999, Lecolier et al, 2006, Lecolier et al, 2007, Garnier et al, 2012, but the findings from these few studies are so far inconclusive.…”
Section: Introductionmentioning
confidence: 99%